Implementation Leadership in the Point of Care Nursing Context: A Systematic Review Comparing Two Measurement Tools - Sonia Angela Castiglione RN, MScA, PhD Candidate; Julie Frechette RN,PhD; V. Ramanakumar Agnihotram PhD (SAGE Publishing, 2023)
Introduction Implementation leadership (IL) are effective point of care (POC) nursing leadership behaviors that facilitate contexts conducive to the successful implementation of evidence-based practices (EBPs). However, no systematic evaluation of IL tools validated for the nursing context existed. Aims The purpose of this systematic review was to compare iterations of two IL measurement tools, the Implementation Leadership Scale (ILS) and the iLEAD, for application in a nursing context; and to critically appraise and summarize the methodological quality of studies assessing their psychometric properties. Methods A comprehensive search was conducted in four databases. Two reviewers independently screened titles and abstracts, reviewed full-text articles, and performed extraction into data tables. Statisticians appraised the quality control aspects. Findings were narratively summarized. Results A total of 247 records were included, where 10 for the ILS (including different versions) and one for the iLEAD met the inclusion criteria. Three studies evaluated the psychometric properties of the ILS in nursing, and its translations into Chinese and Greek. Content validity was deemed to be doubtful for both tools, but the ILS had adequate rating for comprehensiveness; methodological quality was very good for structural validity, internal consistency, hypothesis testing, and responsiveness where applicable for both scales, with the exception of cross-cultural validity which had ratings of adequate and inadequate for versions of the scales. Several study findings met the criteria for good measurement properties. No studies for either tool formally assessed feasibility. Conclusion Applying validated and contextually relevant tools to evaluate the capacity of nursing leadership to engage in IL in real-world contexts are needed. The ILS shows promise but requires further validation for contexts with diverse and multiple nursing leaders at the POC. Feasibility needs to be further studied.